1976
DOI: 10.1128/iai.14.1.88-94.1976
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interferon in ovine and human lymphocyte cultures by mycoplasmas

Abstract: Mycoplasma pneumoniae, Acholeplasma laidlawii, M. arthritidis, and M. pulmonis were shown to induce interferon in the lymphocyte fraction of ovine peripheral blood leukocytes, but not in the polymorphonuclear leukocyte fraction. Human peripheral blood lymphocytes produced significant levels of interferon in response to infection with M. pneumoniae and M. synoviae. The antiviral substance induced by the mycoplasmas in human lymphocytes was characterized as interferon by the usual criteria. 93

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In addition, the persisting high levels of complement-fixing antibody after a single injection of organisms were not consistent with an immunosuppressive response. Furthermore, it has also been shown that viable M. arthritidis is capable of inducing interferon in vivo after injection into mice (27) and in vitro when added to sheep or human lymphocyte cultures (11). More recently, M. pulmonis (9, 21) and M. pneumoniae (4) (glucose utilizers) have been reported to be mitogenic for normal lymphocytes, and additional studies in our laboratories suggest that a wide range of species exhibit this property (7).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the persisting high levels of complement-fixing antibody after a single injection of organisms were not consistent with an immunosuppressive response. Furthermore, it has also been shown that viable M. arthritidis is capable of inducing interferon in vivo after injection into mice (27) and in vitro when added to sheep or human lymphocyte cultures (11). More recently, M. pulmonis (9, 21) and M. pneumoniae (4) (glucose utilizers) have been reported to be mitogenic for normal lymphocytes, and additional studies in our laboratories suggest that a wide range of species exhibit this property (7).…”
Section: Discussionmentioning
confidence: 97%
“…Cole et al (7) have reported that IFN was induced by M. pneumoniae and M. synovie in human lymphocyte cultures, but not by M. salivarium, M. orale, M. gallisepticum and A. laidlawii. They observed a marked variation in the levels of IFN induced by mycoplasmas in lymphocytes from the same donor on different occasions and from different donors in the same experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma membrane lipoproteins may induce the production of proinflammatory cytokines; M. fermentans lipoproteins induce them by stimulation of tyrosine phosphorylation in human monocytes (27). M. synoviae has strong mitogenic activity on mouse lymphocytes and stimulates human lymphocytes to produce interferon (11,13), but it is not known by which component(s). We found that M. synoviae membranes as well as proteins secreted into growth medium have a considerable mitogenic activity in vitro for mouse lymphocytes and chicken thymocytes.…”
mentioning
confidence: 99%